Effect of bradykinin on TGF-β1-induced retinal pigment epithelial cell proliferation and extracellular matrix secretion. Issue 1 (December 2016) - Cai, Wenting; Wei, Qingquan; Liu, Qingyu; Ren, Chengda; Liu, Junling; Zhang, Ruiling; He, Mengmei; Wang, Qianyi; Du, Yaru; Yu, Jing
Abstract Background To evaluate the effect of bradykinin (BK) on TGF-β1-induced retinal pigment epithelial (RPE) cell proliferation and extracellular matrix secretion and to elucidate the relationship between BK and the Erk/Akt signaling pathway. Methods The effects of BK on TGF-β1-induced RPE cell proliferation were examined via CCK-8 assay. Cell culture supernatant collagen I concentrations were measured via ELISA. Fibronectin (Fn), matrix metalloproteinase-2 (MMP-2) and MMP-9 mRNA and protein expression levels were measured via q-PCR and Western blotting, respectively. Changes in Akt/Erk phosphorylation induced by BK and HOE-140 were evaluated via Western blotting. Results TGF-β1 stimulated ARPE-19 cell proliferation, which was inhibited by BK, whose effects were inhibited by HOE-140. BK inhibited TGF-β1-induced collagen I, Fn and MMP-2 secretion in RPE cells, and these effects were inhibited by HOE-140. BK also inhibited TGF-β1-induced Akt phosphorylation in RPE cells, and these effects were blocked by HOE-140. BK had no significant effect on Erk-mediated signaling. Conclusions The findings from this study indicate that BK could be novel therapeutic targets for the treatment of PVR.